2000
DOI: 10.1359/jbmr.2000.15.11.2211
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates Induce Breast Cancer Cell Death In Vitro

Abstract: Breast cancer frequently spreads to bone and is almost always associated with osteolysis. This tumor-induced osteolysis is caused by increased osteoclastic bone resorption. Bisphosphonates are used successfully to inhibit bone resorption in tumor bone disease and may prevent development of new osteolytic lesions. The classical view is that bisphosphonates only act on bone cells. We investigated their effects on breast cancer cells using three human cell lines, namely, MCF-7, T47D, and MDA.MB.231, and we tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
148
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 247 publications
(166 citation statements)
references
References 34 publications
14
148
1
3
Order By: Relevance
“…Bisphosphonates can also decrease the number of bone metastases (Hall and Stoica, 1994;Powles et al, 2002). Moreover, we and others recently demonstrated that, in vitro, bisphosphonates irreversibly reduce breast cancer cell viability by inducing cell death, either by apoptosis or by direct cell necrosis (Fromigue et al, 2000;Senaratne et al, 2000;Jagdev et al, 2001a). The exact mechanism of action of bisphosphonates is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bisphosphonates can also decrease the number of bone metastases (Hall and Stoica, 1994;Powles et al, 2002). Moreover, we and others recently demonstrated that, in vitro, bisphosphonates irreversibly reduce breast cancer cell viability by inducing cell death, either by apoptosis or by direct cell necrosis (Fromigue et al, 2000;Senaratne et al, 2000;Jagdev et al, 2001a). The exact mechanism of action of bisphosphonates is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rats revealed that concentrations as high as 10 À4 M or 10 À3 M can be reached in resorption lacunae (Sato et al, 1991). The concentrations we chose (10 À6 M) could thus be easily reached in the skeleton, and it did not induce strong toxicity in vitro as it can be observed for concentrations of 10 À4 or 10 À3 M (Fromigue et al, 2000). We showed here that this relatively low concentration was able to block growth factors' effects, and to inhibit the 'protective' effect of growth factors on breast cancer cell survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations